ToxR modulates biofilm formation in fish pathogen Vibrio harveyi. (1st February 2022) - Zhang, Y.; Deng, Y.; Feng, J.; Hu, J.; Chen, H.; Guo, Z.; Gao, R.; Su, Y.
Abstract: Vibrio harveyi is a common aquaculture pathogen causing diseases in a variety of aquatic animals. toxR, a conserved virulence‐associated gene in vibrios, is identified in V. harveyi 345, a pathogenic strain isolated from diseased fish. In this study, to gain insight into function of ToxR in V. harveyi, an in‐frame deletion of the toxR gene was constructed to reveal the role of ToxR in the physiology and virulence of V. harveyi . The statistical analysis showed no significant differences in the growth ability, motility, extracellular protease secretion, antibiotic susceptibility, virulence by intraperitoneal injection and the ability of V. harveyi to colonize the spleen and liver tissues of the pearl gentian grouper between the wild‐type (WT) and the toxR mutant. However, the deletion of toxR increased the biofilm formation. The structure of the V . harveyi biofilm was further analysed by using scanning electron microscopy (SEM) and confocal laser scanning microscopy, and the results showed that deletion of toxR increased the number and density of V. harveyi biofilm. Since biofilm production is flagella, exopolysaccharide (EPS) and lipopolysaccharide dependent, 16 of V. harveyi biofilm‐related genes were selected for further analysis. Based on quantitative real‐time reverse transcription‐PCR, the expression levels of these genes, including genes flrB, motY and mshA, flaE, flrA and gmhD, were significantly up‐regulated in the Δ toxR + strain as compared with the WT + and C‐Δ toxR strains during the early and mid‐exponential, while epsG, flaA, flaE, flgD, flgE, flrB, flrC, lpxB, motY, mshA and scrG genes were inhibited because of deletion of the toxR gene in the stationary growth phase. Our results indicate that ToxR plays an important role in controlling the biofilm in V. harveyi .